MODERN IMAGE METHODS FOR RAILWAY CROSSING MONITORING AND CHECKING (Perner's Contacts, 2009)
The content of this article is the description and comparison of security equipments used on railway crossings in the Czech Republic and recommendation of other modern methods.
Keywords: Railway crossings security; camera systems; image processing and preprocessing; image segmentation; image recognition